Attitude, perception and interest of physiotherapy students to participate in geriatrics master’s degree program: a pilot study - Khan, Lubna A.; Parle, Jyoti; Chougle, Sarah (International Journal Of Community Medicine And Public Health, 2022)
Background: Elderly population in India is exponentially increasing due to the impressive gains that society has made in terms of increased life expectancy. With a rise in elderly population, the demand for holistic care also tends to grow. Thus, this study explored interest of physiotherapy students in pursuing further education in geriatric. Methods: A cross sectional study was conducted on 70 physiotherapy interns. They were explained about the purpose of the study and signed consent was taken. Attitude and perception towards geriatric was evaluated using geriatric attitudinal scale (GAS) and a pre-validated self-administered questionnaire was used to assess their interest in pursuing further education in geriatric. Results: Participants typically described positive response towards caring and treating older patients. On analysing few components from GAS, 37% of participants answered as being with elderly is a pleasant feeling while 42% were neutral in their response. 37% of them felt that taking history is not an ordeal and treating them is essential which 30% of the participant was. Despite this only 20% of all students showed interest in pursuing physiotherapy in geriatric. Conclusions: According to our findings, the student’s attitude remained very positive towards the elderly patients but there is undesirable willingness to pursue further education in geriatric.